Quercetin prevent proteoglycan destruction by inhibits matrix metalloproteinase-9, matrix metalloproteinase-13, a disintegrin and metalloproteinase with thrombospondin motifs-5 expressions on osteoarthritis model rats - Dian Agustina Permatasari; Deantari Karliana; Iskandarsyah Iskandarsyah; Ade Arsianti; Anton Bahtiar (Wolters Kluwer Medknow Publications, 2019)
Prior study has shown that Ageratum conyzoides L. extract that containing quercetin has been proved to prevent inflammation and proteoglycan degradation by inhibiting tumor necrosis factor-alpha and matrix metalloproteinase (MMP-9) expression. Target of osteoarthritis (OA) treatment was in the synovial joint that requiring a drug delivery system. The aim of this study was to prove the efficacy of quercetin-loaded lecithin-chitosan nanoparticles on the OA model rats by observed its effect on interleukin (IL-1) β, MMP-9, MMP-13, and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTS-5) expressions. In this study, 70 white male Sprague Dawley rats were divided into 14 groups, 7 groups each for destabilization of medial meniscus (DMM) and monoiodoacetate (MIA)-induced OA. After 28 days from induction, SHAM and negative group received gel base topically; positive group received sodium diclofenac gel; three-dose group received each 0.84, 1.68, 3.36 mg/g quercetin-loaded nanoparticles gel; and A. conyzoides L. group received A. conyzoides L. extract gel. Each group gets treatment until day 70, and then, blood sample was collected for serum analysis; knee joint was isolated and subjected to histology samples treatment. Quercetin-loaded nanoparticle gel dose 1 (0.84 mg/g gel), dose 2 (1.68 mg/g gel), dose 3 (3.36 mg/g), and A. conyzoides L. extract gel could decreased the level of IL-1 β, MMP-9, MMP-13, ADAMTS-5, and increasing color intensity significantly on histopathological observations on DMM and MIA-induced OA.